Happiness in Transition: The Case of Kyrgyzstan - Ceema Namazie; Peter Sanfey (University of Kent, Department of Economics, 1998)
We analyze self-reported measures of satisfaction with life in a transition country, Kyrgyzstan, using 1993 household survey data. We test whether higher levels of satisfaction are associated with greater economic well-being. This hypothesis is strongly supported by the data. Unhappiness is prevalent among older people, the unemployed, and those who are divorced. There appears to be little correlation between happiness and either gender or education level. We find some evidence that income relativities, as measured by perceived position on the wealth ladder, also have a strong effect on life satisfaction.
Keywords: D10; O53; P20; 330; Happiness; Kyrgyzstan; Transition; Welfare; Systemtransformation; Lebensqualität; Soziale Lage; Kirgisistan